p53 Inhibition in Pancreatic Progenitors Enhances the Differentiation of Human Pluripotent Stem Cells into Pancreatic β-Cells - Idil I. Aigha (14913774) (2023)
The multipotent pancreatic progenitor cells (MPCs) co-expressing the transcription factors, PDX1 and NKX6.1, are the source of functional pancreatic β-cells. The aim of this study was to examine the effect of p53 inhibition in MPCs on the generation of PDX1+/NKX6.1+ MPCs and pancreatic β-cell generation. Human embryonic stem cells (hESCs) were differentiated into MPCs and β-cells. hESC-MPCs (stage 4) were treated with different concentrations of p53 inhibitors, and their effect was evaluated using different approaches. NKX6.1 was overexpressed during MPCs specification. Inhibition of p53 using pifithrin-μ (PFT-μ) at the MPC stage resulted in a significant increase in the number of PDX1+/NKX6.1+ cells and a reduction in the number of CHGA+/NKX6.1− cells. Further differentiation of MPCs treated with PFT-μ into pancreatic β-cells showed that PFT-μ treatment did not significantly change the number of C-Peptide+ cells; however, the number of C-PEP+ cells co-expressing glucagon (polyhormonal) was significantly reduced in the PFT-μ treated cells. Interestingly, overexpression of NKX6.1 in hESC-MPCs enhanced the expression of key MPC genes and dramatically suppressed p53 expression. Our findings demonstrated that the p53 inhibition during stage 4 of differentiation enhanced MPC generation, prevented premature endocrine induction and favored the differentiation into monohormonal β-cells. These findings suggest that adding a p53 inhibitor to the differentiation media can significantly enhance the generation of monohormonal β-cells. Other Information Published in: Stem Cell Reviews and Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s12015-023-10509-1